Alteration of haematolocial parameters of "zeol fish"- Clarias batrachus exposed to malathion (Bangladesh Journal of Zoology, 2013)
Clarias batrachus, locally called zeol fish, reared in fresh water on protein diet were exposed to 5% (8.77 mg/l active ingredient) and 10% (17.74 mg/l active ingredient) concentrations of malathion at 24 h intervals, for three weeks in cement tanks containing 580 liters of water with a constant flow (1.5/1 min) of aerated dechlorinated tap water with no recirculation under natural light. Weekly two cc venous blood was drawn from each sample to determine the haematolocial parameters using EDTA (ethylenediamine tetraacetic acid) as an anticoagulant. The findings of this study showed that malathion in different concentrations have some diverse effects on the haematological parameters of Clarias batrachus. Exposer to 10% concentration of malathion was found to have a lethal effect on RBC, thrombocyte, neutrophil and Hb concentration which caused death of the fish with the sign of hypochromic microcytic anemia. Exposer to 5% concentration, on the other hand, showed leucopoenia due to decreased leucocyte counts. Haemoglobin (Hb) concentrations and values of mean corpuscular haemoglobin (MCH), mean corpuscular haemoglobin concentration (MCHC), mean corpuscular volume (MCV) and differential count of WBC levels showed decreased values at 5% concentration of malathion. Significant decrease (P0.05) was observed in the levels of RBC, MCHC, PCV, MCV and WBC. DOI: http://dx.doi.org/10.3329/bjz.v40i2.14311 Bangladesh J. Zool. 40(2): 183-188, 2012